Pengaruh Produk, Harga, Tempat, Promosi Ritel Modern Terhadap Keberlangsungan Usaha Ritel Tradisional di Gresik - Dwiyananda, Ongky Martha; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research was aimed to examine the effect of product, price, place and promotion modern retail to the business continuity of traditional retail business in Gresik. This study used questionnaires in making primary data and quantitative approaches. Tests carried out using multiple linear regression, where the dependent variable (Y) is the business continuity of traditional retail business and the independent variable (X) is the product, price, place,promotion of modern retail. This research sample selected using purposive technique. The sample was 50 traditional retailers radius of two kilometers of modern retail in Gresik.Based on F test results showed that the product, price, place and promotion of modern retail simultaneously significant effect on the sustainability of traditional retail businesses. While the t test results showed that it was only on the variable product, place and promotion that has a significant influence on the sustainability of traditional retail business while at variable rates have no significant effect on the sustainability of traditional retail businesses. Aswe know that modern retail has the advantage of varied products, strategic location and attractive promotion of the suggestions from researchers that the traditional retailers are more creative and innovative in marketing their products and provide better service to the consumer so that the business can continue to compete with modern retail and avoid bakruptcy.